Avaliação, por cintilografia, do refluxo gastroesofágico e do esvaziamento gástrico para líquido e sólido no pré e pós-operatório tardio de pacientes submetidos a By Pass Gástrico em “Y de Roux’’ - Vicente Guerra Filho (2019)
Obesity is a chronic disease that has been increasing worldwide. It is estimated that, in 2035, approximately 69 millions of European adults may be with type 2 diabetes mellitus (T2DM). The gastric bypass Roux-en-Y (GBPRY) is considered the standard technique for treating obesity and even curing Gastroesophageal Reflux (GER). GER’s diagnosis can be performed by esophagogastric scintigraphy. The primary objective of this study was to evaluate prospectively by scintigraphy, the GER and the Gastric Emptying (GE), for liquids and solids, in the pre and postoperative period of patients undergoing a GBPRY. The secondary objectives were to evaluate the impact of GBPRY on the GER and the T2DM. Thirty-seven patients participated in this study being five male ones and 32 female ones, eight with T2DM and 29 normoglycemic people. Age ranged from 18 to 59 years old. Preoperative BMI varied from 35,2 kg/m2 to 55,4 kg/m2 and in the postoperative period of 22,2 kg/m2 to 37,9 kg/m2 (p<0,001). Fasting glucose varied in the preoperative period from 83.0 mg/dl to 165.0 mg/dl and postoperatively from 68.0 mg/dl to 96.0 mg/dl (p < 0.001). Of the patients presenting with preoperative DMT2, it was observed that after BPGYR, all of them controlled blood glucose. Ten patients presented GER preoperatively, two persisted postoperatively and two new cases emerged. The results showed that the group with preoperative GER presented the % Gastric Stump Emptying for Liquids (GSEL) faster than the % Gastric Emptying for Liquids (GEL), with p> 0.05 at ten minutes and % Gastric Stump Emptying for Solids (GSES) was faster than % Gastric Emptying for Solids (GES) at all times evaluated. The group without preoperative GER presented the %GSEL slower than the %GEL from 20 to 120 minutes. In the groups of patients with postoperative GER, the %GSEL was faster than the %GEL from 10 to 50 minutes and the %GSES faster than the %GES 30 minutes up to 2 hours. In relation to the group without postoperative GER, it was observed that %GSEL was slower than% EGL from 20 to 120 minutes and %GSES faster than %GES at all moments of evaluation. Regarding the presence or absence of preoperative T2DM, the group with T2DM presented the %GEL, %GES and %GSES slower than the group without T2DM and that the %GSEL of the group with T2DM was faster than the group without T2DM. The group without T2DM got the %GSEL slower from 20 to 120 minutes with p > 0.05 from 30 minutes. It is concluded that the GBPRY has an important impact on the disappearance of GER. The GEL infers in the presence of GER. The GES does not seem to interfere with the presence of GER. . Patients with T2DM present slower EGL in the preoperative period and faster GSEL postoperatively. Patients with T2DM present slower GEL in the preoperative period and faster GSEL postoperatively.